Drug Repurposing of the Anthelmintic Niclosamide to Treat Multidrug-Resistant Leukemia - Hamdoun, Sami; Jung, Philipp; Efferth, Thomas (Frontiers in Pharmacology, 2017)
Multidrug resistance, a major problem that leads to failure of anticancer chemotherapy, requires the development of new drugs. Repurposing of old drugs is a promising approach for overcoming this problem. An example of such drugs is niclosamide, a known anthelmintic that is now known to be cytotoxic and cytostatic against cancer cells. In this study niclosamide showed varying activity against different cancer cell lines. It revealed better activity against hematological cancer cell lines CCRF-CEM, CEM/ADR5000 and RPMI-8226 compared to the solid tumor cell lines MDA-MB-231, A549 and HT-29. The multidrug resistant CEM/ADR5000 cells conferred cross-sensitivity compared to its sensitive counterpart CCRF-CEM, with a resistance ratio of 1.24. Furthermore, niclosamide caused elevations in reactive oxygen species (ROS) and glutathione levels in leukemia cells. Glutathione synthetase (GS) was predicted as a target of niclosamide. Molecular docking showed that niclosamide probably binds to the ATP- binding site of GS with a binding energy of -9.40 kcal/mol. Using microscale thermophoresis, the binding affinity between niclosamide an recombinant human GS was measured, which gave a binding constant of 5.64 μM. COMPARE analyses of the NCI microarray database for 60 cell lines showed that several genes, including those involved in lipid metabolism, correlated with cellular responsiveness to niclosamide. Hierarchical cluster analysis showed five major branches with significant differences between sensitive and resistant cell lines (p= 8.66 × 105). Niclosamide significantly decreased NFAT activity as predicted by promoter binding motif analysis. In conclusion, niclosamide is more active against hematological malignancies compared to solid tumors. It is particularly active against the multidrug-resistant CEM/ADR 5000 leukemia cells. Inhibition of glutathione synthesis and NFAT signaling are two more mechanisms for the anticancer activity of niclosamide. Gene expression profiling can be used to predict the sensitivity or resistance of cancer cells to niclosamide.